2021
DOI: 10.32890/mjli2021.18.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Mobile Addiction, Interpersonal Relationship, and Academic Behavior Among Young Adults in Tertiary Institutions

Abstract: Purpose – Smartphones have become part and parcel of life in the 21st century. Since there has been limited research exploring the relationship between mobile addiction, interpersonal relationship, and academic behaviour among young adults in tertiary institutions, the present study has embarked on an exploration of the relationship between these three variables in the Malaysian higher education context. Methodology – A descriptive correlational research design was employed to collect and analyse the data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…It was also reported that several interpersonal relationship problems might arise from this addiction, namely the development of low self-esteem, extroversion, higher approval motivation, and higher self-monitoring. Such an impact can be unfavourable for those who need the interpersonal skills essential for their future (Fook et al, 2021). Every relationship is different.…”
Section: Establishing Student Interpersonal Relationsmentioning
confidence: 99%
“…It was also reported that several interpersonal relationship problems might arise from this addiction, namely the development of low self-esteem, extroversion, higher approval motivation, and higher self-monitoring. Such an impact can be unfavourable for those who need the interpersonal skills essential for their future (Fook et al, 2021). Every relationship is different.…”
Section: Establishing Student Interpersonal Relationsmentioning
confidence: 99%
“…According to Fook et al (2021), mobile addiction can increase sensitivity to interpersonal relationships and negative feelings. Research by Chiu (2014) suggests that addiction can be linked to social and environmental factors, such as parent-child relationships, communication styles, attachment styles, friendships, school adjustments, academic achievement, and psychological factors like impulsiveness, depressive symptoms, isolation, self-confidence, selfworth, and anxiety.…”
Section: Smartphones Addiction and Interpersonal Relationshipmentioning
confidence: 99%
“…Studies have shown a correlation between smartphone addiction and students' academic performance, with some studies indicating a link between smartphone use and academic achievement (Boumosleh & Jaalouk, 2017;Fook et al, 2021;Kubrusly et al, 2021). Others have explored the relationship between cellphone addiction, interpersonal relationships and academic behavior in young individuals.…”
Section: Smart Phone Addiction Interpersonal Relationship and Academi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of ICT may improve the teaching experience, the quality of higher education, and the academic accomplishment of students (Shaheen & Khatoon, 2017). Notwithstanding, the intricacies of technology linked to ICT usage in the teaching and learning methodology may have contributed to students' incapability of dealing with the remarkably complex technological advancements in a healthy manner, potentially resulting in health issues such as recurring vision problems, headaches, hypertension, cardiovascular problems, and psychiatric illnesses (Fook et al, 2021;Park et al, 2020;Tams et al, 2013). The recent COVID-19 outbreak has caused a dramatic shift in the Malaysian educational landscape as the online learning policy has been fully implemented to substitute the conventional direct teaching and learning methods (Solhi, 2020).…”
Section: Introductionmentioning
confidence: 99%